Water-based carbon-coated electrode ink for printable flexible micro-current galvanic cells
Patent Information
- Application Number
- CN202610817339.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-08
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种可印刷柔性微电流原电池用水性碳包覆电极油墨,解决了现阶段电极油墨无法满足轻量化柔性电子的应用需求的问题
[0014]本发明的有益效果:本发明采用导电炭黑、鳞片石墨与碳纳米管复配构建三维导电网络,在提升电极整体导电性、加快电子传输速率的同时,实现对锌锰活性物质的均匀包覆,针对二氧化锰正极,可缓冲电化学反应过程中的体积变化,抑制活性物质粉化与团聚;针对锌负极,可形成均匀保护层,减少锌枝晶生长与局部腐蚀,降低副反应发生风险。制备电极油墨电流、电压稳定性优异,单位面积印刷电极,电流可达毫安级。同时,本发明采用纯水性配方体系,以水为分散介质,无有机溶剂添加,避免了VOCs排放风险,可适配食品接触、贴身可穿戴、医用护理等对安全性要求较高的应用场景。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode ink preparation technology, specifically to an aqueous carbon-coated electrode ink for printable flexible microcurrent galvanic cells. Background Technology
[0002] Self-generated microcurrent technology has shown broad application prospects in flexible electronics, wearable devices, disposable electronic tags, and low-power IoT sensing nodes. Currently, the mainstream self-generated microcurrent technologies in the field of flexible electronics mainly include piezoelectric, triboelectric, thermoelectric, and traditional thin-film battery technologies. Among them, piezoelectric and triboelectric technologies rely on the conversion of mechanical energy into electrical energy, while thermoelectric technologies are based on temperature difference power generation. These technologies generally have defects such as weak output current, poor stability, susceptibility to environmental temperature, humidity, and vibration conditions, and insufficient continuous power supply capacity, making it difficult to meet the long-term use requirements of most low-power devices for stable microcurrents. While traditional thin-film batteries have stable output, their manufacturing process is complex and costly, and their flexibility is poor, limiting their large-scale application in disposable and lightweight scenarios.
[0003] Zinc-manganese batteries, with their low cost, stable voltage platform, and mature and reliable system, have become one of the preferred electrochemical systems for low-power flexible applications. Compared with other self-generating technologies, they can provide stable micro-current output without relying on environmental energy input, making them suitable for a wider range of scenarios. However, existing zinc-manganese systems still face several bottlenecks in flexible applications: the volume change rate of manganese dioxide cathodes can reach 20%-30% during the reaction, making them prone to pulverization and agglomeration; zinc anodes are prone to dendrite growth and localized corrosion, leading to battery short-circuit failure; traditional rigid packaging and fabrication processes are difficult to adapt to flexible substrates, and there is a lack of low-cost, printable electrode fabrication solutions, failing to meet the application requirements of disposable, lightweight flexible electronics. To address these issues, this invention proposes a printable aqueous electrode ink solution adapted to the zinc-manganese system, enabling the fabrication of a low-cost, stable output flexible self-generating micro-current device. Summary of the Invention
[0004] The purpose of this invention is to provide a water-based carbon-coated electrode ink for printable flexible microcurrent primary batteries, which solves the problem that current electrode inks cannot meet the application requirements of lightweight flexible electronics.
[0005] The objective of this invention can be achieved through the following technical solutions: A printable flexible microcurrent primary cell with water-based carbon-coated electrode ink, including positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 5-10 parts dispersant, 10-15 parts resin, 15-20 parts additives, 35-40 parts deionized water, 2-6 parts conductive carbon black, 5-7 parts graphite, 1-3 parts carbon nanotubes, and 15-27 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 4-11 parts dispersant, 5-14 parts resin, 10-15 parts additives, 30-37 parts deionized water, 4-5 parts conductive carbon black, 6-9 parts graphite, 1-2 parts carbon nanotubes, 3-7 parts reducing agent, and 11-19 parts spherical zinc powder.
[0006] Furthermore, the positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to neutral, and disperse for 30-60 minutes at a speed of 3000-5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60-90 minutes at a rotation speed of 2000-4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 30-60 minutes to obtain water-based carbon-coated positive electrode ink.
[0007] Furthermore, the negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH to neutral, and disperse for 30-60 minutes at a speed of 3000-5000 r / min to obtain the negative electrode pre-dispersion. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60-90 minutes at a rotation speed of 1000-3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 15-30 minutes to obtain water-based carbon-coated negative electrode ink.
[0008] Furthermore, the reducing agent is one or more of glucose, fructose, lactose, maltose, vitamin C, isoascorbic acid, sodium citrate, chitosan, PVP, and CMC in any proportion.
[0009] Furthermore, the particle size of the spherical zinc powder is 3-8 μm.
[0010] Furthermore, the dispersant is a sterically hindered aqueous dispersant.
[0011] Furthermore, the resin is a water-based acrylic resin with a pH of 6-7 and a film-forming property of ≥90%. Furthermore, the additive is prepared by mixing a rheology modifier and a slow-drying agent.
[0012] Furthermore, the rheology modifier is one or more of the following in any proportion: waterborne polyurethane rheology modifier, hydrophobically modified alkali-swellable acrylic, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.
[0013] Furthermore, the slow-drying agent is one or more of dipropylene glycol methyl ether, tripropylene glycol methyl ether, propylene glycol, diethylene glycol butyl ether, and aqueous alcohol ester twelve, mixed in any proportion.
[0014] The beneficial effects of this invention are as follows: This invention utilizes a composite of conductive carbon black, flake graphite, and carbon nanotubes to construct a three-dimensional conductive network. This enhances the overall conductivity of the electrode, accelerates electron transport, and simultaneously achieves uniform coating of zinc and manganese active materials. For the manganese dioxide cathode, it buffers volume changes during the electrochemical reaction process, inhibiting the pulverization and agglomeration of the active materials. For the zinc anode, it forms a uniform protective layer, reducing zinc dendrite growth and localized corrosion, and lowering the risk of side reactions. The prepared electrode ink exhibits excellent current and voltage stability; the printed electrode per unit area can achieve milliampere-level current. Furthermore, this invention employs a pure aqueous formulation system, using water as the dispersion medium, without the addition of organic solvents, thus avoiding the risk of VOC emissions. This makes it suitable for applications with high safety requirements, such as food contact, wearable devices, and medical care.
[0015] By adjusting the ratio of carbon materials to Zn / MnO2, as well as the ratio of dispersants, resins, and additives, the preparation process can be modified to achieve a wide range of adjustments to the ink's solid content, viscosity, and rheological properties. This allows it to be adapted to various printing processes such as screen printing, gravure printing, and doctor blade coating. Simultaneously, through the synergistic effect of adhesion promoters and silane coupling agents, the ink can form a uniform and stable electrode coating on various porous or flexible substrates such as medical nonwoven fabrics, pure cotton fabrics, hydrogels, paper, and flexible polymers. This eliminates the need for additional conductive substrates or complex encapsulation processes, making it suitable for large-area, low-cost, large-scale preparation.
[0016] The electrodes require no pre-activation treatment; contact with an ion-containing liquid medium triggers a galvanic cell reaction. Body fluids (blood, urine, saliva, etc.), electrolyte solutions, and ion-containing water can all serve as activation media, generating a stable microcurrent output. This characteristic allows the invention to be adapted to various scenarios such as wetness alarm devices, microcurrent dressings for wounds, body fluid monitoring tags, and emergency low-power sensing nodes, overcoming the limitations of traditional self-generating technologies that require specific activation conditions.
[0017] Using β-manganese dioxide, the structure is stable and the conductivity is excellent, which suppresses the volume expansion and pulverization during charging and discharging, and improves the stability of microcurrent output.
[0018] The zinc powder is limited to 3-8μm spherical shape, with moderate specific surface area and uniform dispersion, reducing the risk of localized corrosion and dendrite formation.
[0019] The reducing agent can reduce zinc ions in situ, inhibit zinc dendrite growth, reduce local corrosion and biotoxicity, and improve electrode output stability and safety.
[0020] The dispersant forms a steric hindrance layer on the particle surface through long-chain polymers, achieving strong adsorption, high dispersion, and anti-agglomeration, which significantly improves grinding efficiency and ink storage stability.
[0021] With low addition amount and wide adjustment range, the rheology modifier can precisely control the thixotropy and leveling properties of ink, and is suitable for various processes such as screen printing, gravure printing, and doctor blade coating.
[0022] Slow-drying agents are used to adjust the drying rate, reduce surface tension, improve printability and transferability, and prevent screen clogging / pinholes. They are suitable for a variety of substrates such as porous nonwoven fabrics, textiles, and hydrogels.
[0023] The entire system of dispersants, resins, and additives is synergistically adjusted to a pH of 6.5-7.5, making it near-neutral, non-irritating, and suitable for medical non-woven fabrics and skin contact. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 18 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 4 parts reducing agent, and 14 parts spherical zinc powder.
[0026] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 6.5, and disperse for 30 minutes at a speed of 3000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60 min at a rotation speed of 2000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 35 minutes to obtain water-based carbon-coated positive electrode ink.
[0027] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0028] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0029] The slow-drying agent is dipropylene glycol methyl ether.
[0030] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 6.5, and disperse for 30 min at a speed of 3000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60 min at a rotation speed of 1000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 15 minutes to obtain water-based carbon-coated negative electrode ink.
[0031] The reducing agent is glucose.
[0032] The spherical zinc powder has a particle size of 3 μm.
[0033] The dispersant is a sterically hindered, water-based dispersant.
[0034] The resin is an aqueous acrylic resin with pH=6 and film-forming properties ≥90%.
[0035] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0036] The rheology modifier is hydroxyethyl cellulose.
[0037] The slow-drying agent is propylene glycol.
[0038] Example 2: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 18 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 4 parts reducing agent, and 14 parts spherical zinc powder.
[0039] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 6.5, and disperse for 35 minutes at a speed of 3000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60 min at a rotation speed of 2000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 35 minutes to obtain water-based carbon-coated positive electrode ink.
[0040] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0041] The rheology modifier is a water-based polyurethane rheology modifier.
[0042] The slow-drying agent is tripropylene glycol methyl ether.
[0043] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 6.5, and disperse for 30 min at a speed of 3000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60 min at a rotation speed of 1000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 15 minutes to obtain water-based carbon-coated negative electrode ink.
[0044] The reducing agent mentioned is vitamin C.
[0045] The spherical zinc powder has a particle size of 3 μm.
[0046] The dispersant is a sterically hindered, water-based dispersant.
[0047] The resin is an aqueous acrylic resin with a pH of 6-7 and a film-forming property of ≥90%.
[0048] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0049] The rheology modifier is hydroxypropyl methylcellulose.
[0050] The slow-drying agent is aqueous alcohol ester twelve.
[0051] Example 3: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 21 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 4 parts reducing agent, and 15 parts spherical zinc powder.
[0052] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 6.5, and disperse for 40 minutes at a speed of 3000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60 min at a rotation speed of 2000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 40 minutes to obtain water-based carbon-coated positive electrode ink.
[0053] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0054] The rheology modifier is hydroxypropyl methylcellulose.
[0055] The slow-drying agent is propylene glycol.
[0056] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 6.5, and disperse for 30 min at a speed of 3000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60 min at a rotation speed of 1000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 20 minutes to obtain water-based carbon-coated negative electrode ink.
[0057] The reducing agent is fructose.
[0058] The spherical zinc powder has a particle size of 3 μm.
[0059] The dispersant is a sterically hindered, water-based dispersant.
[0060] The resin is an aqueous acrylic resin with pH=6 and film-forming properties ≥90%.
[0061] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0062] The rheology modifier is a water-based polyurethane rheology modifier.
[0063] The slow-drying agent is diethylene glycol butyl ether.
[0064] Example 4: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 24 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 5 parts reducing agent, and 16 parts spherical zinc powder.
[0065] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7, and disperse for 40 minutes at a speed of 3000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60 min at a rotation speed of 2000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 45 minutes to obtain water-based carbon-coated positive electrode ink.
[0066] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0067] The rheology modifier is hydroxyethyl cellulose.
[0068] The slow-drying agent is a water-based alcohol ester twelve.
[0069] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 7, and disperse for 30 min at a speed of 3000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60 min at a rotation speed of 1000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 20 minutes to obtain water-based carbon-coated negative electrode ink.
[0070] The reducing agent is isoascorbic acid.
[0071] The spherical zinc powder has a particle size of 5 μm.
[0072] The dispersant is a sterically hindered, water-based dispersant.
[0073] The resin is an aqueous acrylic resin with pH=6 and film-forming properties ≥90%.
[0074] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0075] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0076] The slow-drying agent is tripropylene glycol methyl ether.
[0077] Example 5: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary battery, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 27 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 5 parts reducing agent, and 17 parts spherical zinc powder.
[0078] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7, and disperse for 45 minutes at a speed of 3000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60 min at a rotation speed of 2000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 50 minutes to obtain water-based carbon-coated positive electrode ink.
[0079] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0080] The rheology modifier is a water-based polyurethane rheology modifier.
[0081] The slow-drying agent is dipropylene glycol methyl ether.
[0082] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 7, and disperse for 30 min at a speed of 3000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60 min at a rotation speed of 1000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 25 minutes to obtain water-based carbon-coated negative electrode ink.
[0083] The reducing agent is sodium citrate.
[0084] The spherical zinc powder has a particle size of 5 μm.
[0085] The dispersant is a sterically hindered, water-based dispersant.
[0086] The resin is an aqueous acrylic resin with pH=6 and film-forming properties ≥90%.
[0087] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0088] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0089] The slow-drying agent is propylene glycol.
[0090] Example 6: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising a positive electrode ink and a negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 26 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, 6 parts reducing agent, and 18 parts spherical zinc powder.
[0091] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7, and disperse for 50 min at a speed of 5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 90 min at a rotation speed of 4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 60 minutes to obtain water-based carbon-coated positive electrode ink.
[0092] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0093] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0094] The slow-drying agent is diethylene glycol butyl ether.
[0095] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 7, and disperse for 30 minutes at a speed of 5000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 90 min at a rotation speed of 3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 30 minutes to obtain water-based carbon-coated negative electrode ink.
[0096] The reducing agent is chitosan.
[0097] The spherical zinc powder has a particle size of 5 μm.
[0098] The dispersant is a sterically hindered, water-based dispersant.
[0099] The resin is an aqueous acrylic resin with pH=7 and film-forming properties ≥90%.
[0100] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0101] The rheology modifier is hydroxyethyl cellulose.
[0102] The slow-drying agent is a water-based alcohol ester twelve.
[0103] Example 7: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 18 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 5 parts reducing agent, and 16 parts spherical zinc powder.
[0104] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7, and disperse for 35 minutes at a speed of 5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 90 min at a rotation speed of 4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 35 minutes to obtain water-based carbon-coated positive electrode ink.
[0105] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0106] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0107] The slow-drying agent is tripropylene glycol methyl ether.
[0108] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH value to 7, and disperse for 30 minutes at a speed of 5000 r / min to obtain the negative electrode predispersant. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 90 min at a rotation speed of 3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 20 minutes to obtain water-based carbon-coated negative electrode ink.
[0109] The reducing agent is PVP.
[0110] The spherical zinc powder has a particle size of 5 μm.
[0111] The dispersant is a sterically hindered, water-based dispersant.
[0112] The resin is an aqueous acrylic resin with pH=7 and film-forming properties ≥90%.
[0113] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0114] The rheology modifier is a water-based polyurethane rheology modifier.
[0115] The slow-drying agent is dipropylene glycol methyl ether.
[0116] Example 8: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 24 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 4 parts reducing agent, and 14 parts spherical zinc powder.
[0117] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7.5, and disperse for 40 minutes at a speed of 5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 90 min at a rotation speed of 4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 45 minutes to obtain water-based carbon-coated positive electrode ink.
[0118] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0119] The rheology modifier is hydroxyethyl cellulose.
[0120] The slow-drying agent is propylene glycol.
[0121] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH to 7.5, and disperse for 30 minutes at a speed of 5000 r / min to obtain the negative electrode pre-dispersion. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 90 min at a rotation speed of 3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 15 minutes to obtain water-based carbon-coated negative electrode ink.
[0122] The reducing agent is lactose.
[0123] The spherical zinc powder has a particle size of 8 μm.
[0124] The dispersant is a sterically hindered, water-based dispersant.
[0125] The resin is an aqueous acrylic resin with pH=7 and film-forming properties ≥90%.
[0126] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0127] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0128] The slow-drying agent is diethylene glycol butyl ether.
[0129] Example 9: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising a positive electrode ink and a negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 27 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 5 parts reducing agent, and 15 parts spherical zinc powder.
[0130] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7.5, and disperse for 45 minutes at a speed of 5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 90 min at a rotation speed of 4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 50 minutes to obtain water-based carbon-coated positive electrode ink.
[0131] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0132] The rheology modifier is a water-based polyurethane rheology modifier.
[0133] The slow-drying agent is a water-based alcohol ester twelve.
[0134] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH to 7.5, and disperse for 30 minutes at a speed of 5000 r / min to obtain the negative electrode pre-dispersion. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 90 min at a rotation speed of 3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 20 minutes to obtain water-based carbon-coated negative electrode ink.
[0135] The reducing agent is maltose.
[0136] The spherical zinc powder has a particle size of 8 μm.
[0137] The dispersant is a sterically hindered, water-based dispersant.
[0138] The resin is an aqueous acrylic resin with pH=7 and film-forming properties ≥90%.
[0139] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0140] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0141] The slow-drying agent is tripropylene glycol methyl ether.
[0142] Example 10: A water-based carbon-coated electrode ink for a printable flexible microcurrent primary cell, comprising positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 12 parts resin, 18 parts additives, 37 parts deionized water, 4 parts conductive carbon black, 6 parts graphite, 2 parts carbon nanotubes, and 21 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 8 parts dispersant, 10 parts resin, 13 parts additives, 34 parts deionized water, 5 parts conductive carbon black, 8 parts graphite, 2 parts carbon nanotubes, 6 parts reducing agent, and 18 parts spherical zinc powder.
[0143] The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to 7.5, and disperse for 40 minutes at a speed of 5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 90 min at a rotation speed of 4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 40 minutes to obtain water-based carbon-coated positive electrode ink.
[0144] The additive mentioned in step A1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0145] The rheology modifier is a hydrophobically modified alkali-swellable acrylic acid.
[0146] The slow-drying agent is dipropylene glycol methyl ether.
[0147] The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH to 7.5, and disperse for 30 minutes at a speed of 5000 r / min to obtain the negative electrode pre-dispersion. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 90 min at a rotation speed of 3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 25 minutes to obtain water-based carbon-coated negative electrode ink.
[0148] The reducing agent is CMC.
[0149] The spherical zinc powder has a particle size of 8 μm.
[0150] The dispersant is a sterically hindered, water-based dispersant.
[0151] The resin is an aqueous acrylic resin with pH=7 and film-forming properties ≥90%.
[0152] The additive mentioned in step B1 is prepared by mixing a rheology modifier and a slow-drying agent.
[0153] The rheology modifier is hydroxyethyl cellulose.
[0154] The slow-drying agent is propylene glycol.
[0155] The inks prepared in Examples 1-10 were screen printed on medical nonwoven fabric as the substrate to make experimental samples. 0.9% physiological saline was used as the electrolyte, the electrode size was 0.5cm×2cm, the electrode spacing was 1cm, the test time was 30min, the viscosity test temperature was 25℃, the adhesion was measured by the cross-cut method residual rate, and the thickness was measured by the dry film thickness of the printed electrode. The performance was tested, and the test results are shown in Table 1 below.
[0156] Table 1
[0157] As shown in Table 1, this application can meet the application requirements of lightweight flexible electronics.
[0158] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells, characterized in that: Including positive electrode ink and negative electrode ink; The positive electrode ink comprises the following raw materials in parts by weight: 5-10 parts dispersant, 10-15 parts resin, 15-20 parts additives, 35-40 parts deionized water, 2-6 parts conductive carbon black, 5-7 parts graphite, 1-3 parts carbon nanotubes, and 15-27 parts β-manganese dioxide. The negative electrode ink comprises the following raw materials in parts by weight: 4-11 parts dispersant, 5-14 parts resin, 10-15 parts additives, 30-37 parts deionized water, 4-5 parts conductive carbon black, 6-9 parts graphite, 1-2 parts carbon nanotubes, 3-7 parts reducing agent, and 11-19 parts spherical zinc powder.
2. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 1, characterized in that: The positive electrode ink is prepared by the following steps: Step A1: Mix the dispersant, resin, additives and deionized water, adjust the pH to neutral, and disperse for 30-60 minutes at a speed of 3000-5000 r / min to obtain the positive electrode predispersant. Step A2: Add conductive carbon black, graphite, carbon nanotubes, β-manganese dioxide and glass beads to the positive electrode pre-dispersion solution, and disperse for 60-90 minutes at a rotation speed of 2000-4000 r / min to obtain dispersed positive electrode ink. Step A3: Filter the dispersed positive electrode ink to remove glass beads and obtain primary positive electrode ink. Grind the primary positive electrode ink for 30-60 minutes to obtain water-based carbon-coated positive electrode ink.
3. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 1, characterized in that: The negative electrode ink is prepared by the following steps: Step B1: Mix the dispersant, resin, additives, reducing agent and deionized water, adjust the pH to neutral, and disperse for 30-60 minutes at a speed of 3000-5000 r / min to obtain the negative electrode pre-dispersion. Step B2: Add conductive carbon black, graphite, carbon nanotubes, spherical zinc powder and glass beads to the negative electrode pre-dispersion liquid, and disperse for 60-90 minutes at a rotation speed of 1000-3000 r / min to obtain dispersed negative electrode ink. Step B3: Filter the dispersed negative electrode ink to remove glass beads and obtain primary negative electrode ink. Grind the primary positive electrode ink for 15-30 minutes to obtain water-based carbon-coated negative electrode ink.
4. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 3, characterized in that: The reducing agent is one or more of glucose, fructose, lactose, maltose, vitamin C, isoascorbic acid, sodium citrate, chitosan, PVP, and CMC in any proportion.
5. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 3, characterized in that: The spherical zinc powder has a particle size of 3-8 μm.
6. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 1, characterized in that: The dispersant is a sterically hindered, water-based dispersant.
7. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 1, characterized in that: The resin is a water-based acrylic resin.
8. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 1, characterized in that: The additive is prepared by mixing a rheology modifier and a slow-drying agent.
9. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 8, characterized in that: The rheology modifier is one or more of the following in any proportion: waterborne polyurethane rheology modifier, hydrophobically modified alkali-swellable acrylic, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.
10. The water-based carbon-coated electrode ink for printable flexible microcurrent galvanic cells according to claim 8, characterized in that: The slow-drying agent is one or more of dipropylene glycol methyl ether, tripropylene glycol methyl ether, propylene glycol, diethylene glycol butyl ether, and aqueous alcohol ester twelve, mixed in any proportion.